Overview of applied methods for sustainable hydropower development at riverscale extent - Panovska F., Mitovski S., Petkovski L. (Slovenian National Comitee on Large Dams- SLOCOLD, Macedonian Committee on Large Dams - MACOLD, 2020)
onsidering latest rising temperatures of the atmosphere and increasing effect of burning fossil fuels for energy, climate has shifted and we have all witnessed unusual weather conditions. Since awareness has been raised on producing electricity with burning the fossils, water is seen on as a very reliable resource for renewable hydropower generation. It can cover peak hours electricity demands, but it can also cover base energy demands – unlike sun or wind energy which are highly unpredictable renewables in space and time. Human activities have polluted available fresh water, and rising population needs more and more by the day to survive. Agriculture is thriving and needs more water than ever to feed the growing population. However, as much as we need it, we also need to protect our homes from flash flood events occurring more and more often. This and more presents a picture of a very complex water resources systems planning and management problem. Every system needs to be planned with taking under consideration all related stakeholders.